A pH-responsive chitosan medical bioadhesive and its preparation and application method
By mixing phenylboric acid modified chitosan, polyphenol compounds, crosslinking agents and polyethylene glycol in aqueous solution, pH-responsive chitosan medical bioadhesives are solved, and the problem of insufficient adhesion of existing bioadhesives in humid environments is achieved, and efficient wound healing support and personalized degradation control is achieved.
Patent Information
- Application Number
- CN202510019095.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The existing bioadhesives have insufficient adhesion in humid environments, making it difficult to effectively support wound closure, and the preparation process is complicated, resulting in biotoxicity problems.
By mixing phenylboric acid modified chitosan, polyphenol compounds, crosslinking agents and polyethylene glycol in an aqueous solution, a pH-responsive chitosan medical bioadhesive agent has the characteristics of controlling degradability and improving wet adhesion properties.
It achieves high adhesion performance under wet conditions, provides personalized wound healing support, reduces the risk of infection, is non-toxic and harmless, and is suitable for use in humans.
Smart Images

Figure CN119405872B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bioadhesives, and in particular to a pH-responsive chitosan medical bioadhesive and a preparation and application method thereof. Background Art
[0002] When the skin suffers a major injury, rapid wound treatment is crucial, not only to prevent infection but also to promote wound healing. Wound healing is a complex process that includes four key stages: hemostasis, inflammation, proliferation, and remodeling. In medical practice, bioadhesives, as an innovative means of wound closure and hemostasis, have shown the advantages of ease of use, rapid closure, and less tissue damage compared to traditional sutures and staples. They promote healing and control bleeding by connecting tissues, and therefore have been widely recognized in clinical applications.
[0003] However, the adhesion of bioadhesives in a wet environment remains a technical challenge. The hydration layer caused by the liquid may hinder the adhesion of the adhesive to the tissue, resulting in a decrease in adhesion. At present, medical adhesives still have deficiencies in adhesion to blood and adipose tissue. Therefore, improving their adhesion properties under wet conditions has become a hot topic of research. pH-responsive materials usually introduce phenylboronic acid groups. Since the phenylboronic acid groups bind to sugar compounds on biological cell membranes, the materials are endowed with certain cell adhesion, but this adhesion strength is not enough to support wound closure. There have been attempts at a variety of biomacromolecule medical adhesives on the market. For example, in the patent "A method for preparing a medical adhesive" (Announcement No.: CN106512078A), a medical adhesive is prepared by using xanthan gum, mussel mucin and lard. Although this method has certain innovations, its preparation process is relatively complicated, and it fails to give full play to the advantages of biomacromolecules, and the adhesion performance needs to be improved. Another patent, "A novel polysaccharide cellulose medical glue with high mechanical strength and wound healing promotion and its preparation method" (Announcement No.: CN106110376A), introduces a polysaccharide cellulose medical glue made from sodium carboxymethyl cellulose, astragalus polysaccharide, polyurethane modified starch adhesive, sodium alginate and water for injection. Although this adhesive has potential in mechanical strength and wound healing promotion, its product has biological toxicity problems, which limits its application in the field of human medicine.
[0004] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0005] The first purpose of the present invention is to uniformly mix phenylboronic acid-modified chitosan, polyphenol compounds, cross-linking agents with different functional groups and polyethylene glycols with different molecular weights in an aqueous solution to obtain a pH-responsive chitosan medical bioadhesive under alkaline conditions. This not only effectively solves the problem of insufficient adhesion strength of current bioadhesives in vivo, but also has the advantages of being non-toxic, harmless and controllably degradable, solving the problem of secondary suture removal for patients.
[0006] The above technical objectives of the present invention are achieved through the following technical solutions:
[0007] A pH-responsive chitosan medical bioadhesive comprises phenylboronic acid-modified chitosan, a polyphenol compound, a pH regulator, a crosslinking agent and polyethylene glycol; the mass concentration of the phenylboronic acid-modified chitosan is 1.3-13% w / w; the mass concentration of the polyphenol compound is 0.1-2% w / w; the mass concentration of the crosslinking agent is 0.2-2% w / w; the mass concentration of the polyethylene glycol is 1.0-10.4% w / w; and the pH regulator regulates the pH in the system to 7.5-8.
[0008] Preferably, the mass concentration of the phenylboronic acid modified chitosan is 2% w / w; the mass concentration of the polyphenol compound is 1% w / w; the mass concentration of the cross-linking agent is 0.3% w / w; the mass concentration of the polyethylene glycol is 1.6% w / w; and the pH regulator adjusts the pH in the system to 7.6.
[0009] Chitosan (CS) is a polysaccharide derived from deacetylated chitin, and its molecular structure is rich in active functional groups such as amino and hydroxyl groups. As the second largest natural renewable polymer material after cellulose in nature, chitosan has shown great application potential in the biomedical field due to its biodegradability, biocompatibility, excellent antibacterial properties, easy formation of complexes with metal ions, and molecular modification. Materials prepared using chitosan can not only make full use of the excellent properties of natural polymers, but also give the materials excellent mechanical strength, which makes chitosan medical bioadhesives occupy an important position in the future of biomaterials science and medical health industry, and show broad prospects for commercialization and clinical application.
[0010] In the present invention, phenylboronic acid modification imparts pH responsiveness to chitosan. Phenylboronic acid groups form dynamically reversible covalent bonds with polyphenol compounds, so that the adhesive can adjust its crosslinking density and degradation characteristics under different pH conditions. By adjusting the pH, the reversible reaction between the phenylboronic acid groups and the polyphenol compounds can be controlled, thereby achieving degradation or curing of the adhesive. At the same time, the polyphenol compounds can form hydrogen bonds or coordination bonds with the amino groups on the chitosan chain, and these weak interactions help to improve the mechanical properties and adhesion properties of the adhesive. The hydrophilic functional groups of the polyethylene glycol molecular chain can form hydrogen bonds with water molecules, reduce the water molecule layer at the interface, and thus reduce the negative impact of the hydration layer on the adhesion between the adhesive and the tissue. The introduction of polyethylene glycol can also improve the flexibility and ductility of the adhesive, help the adhesive to better adapt to the irregular surface of the tissue, and increase the adhesion area and adhesion. When the environmental pH changes, these weak interactions can be destroyed or re-formed, so that the network structure of the adhesive changes, thereby regulating the degradation rate of the adhesive.
[0011] In the present invention, the adhesive can dynamically adjust its structure and degradation rate under different pH conditions at different stages of wound healing. In the early stage of wound healing, the environment is more acidic and the pH is lower, so the degradation rate of the adhesive is slower, which helps to protect the wound surface. In the later stage of healing, the pH gradually increases to neutral or weakly alkaline, and the degradation rate of the adhesive is accelerated, which helps to remove the adhesive and promote complete healing of the tissue. The present invention can provide a more personalized medical solution by controlling the degradation rate of the adhesive and adjusting the residual time of the adhesive in the body according to the actual wound healing needs. This precise degradation rate control helps to provide continuous protection in the early stages of wound healing and reduce interference with new tissue in the later stages of healing.
[0012] Preferably, the polyphenolic compounds include one or more of tea phenol, gallic acid, tannic acid, tannic acid, catechin, 3,4-dihydroxyphenylacetic acid, 2,3-dihydroxybenzoic acid, and dopamine. Polyphenolic compounds have strong antioxidant and free radical scavenging abilities, which help to reduce the oxidative stress response of tissues around wounds, protect cells from free radical damage, and promote cell regeneration and wound healing. For example, tea phenol and tannic acid have natural antibacterial properties, which can inhibit the growth of pathogenic microorganisms and reduce the risk of infection. Catechins, tannic acid, etc. can accelerate the repair and healing of skin and tissues by regulating cell proliferation and migration; at the same time, they regulate inflammatory responses, thereby helping to balance the inflammatory and repair stages in the wound healing process.
[0013] Preferably, the cross-linking agent is one or more of genipin, glutaraldehyde, 2,5-furandicarboxaldehyde, ethylene glycol diglycidyl ether, polypropylene glycol glycidyl ether, trisphenol methane triglycidyl ether, isophorone diisocyanate, and toluene diisocyanate. By enhancing the interaction between molecules, the adhesive can be more firmly adhered to the surface of moist or complex biological tissues, thereby improving its adhesion strength and durability. The selection and use concentration of the cross-linking agent can accurately control the degradation rate of the adhesive. The higher the cross-linking density, the slower the degradation rate of the adhesive; on the contrary, when the cross-linking density is low, the degradation rate is faster. The degradation time of the adhesive in the body can be adjusted according to the healing needs of different wounds to achieve personalized medical solutions.
[0014] Preferably, the polyethylene glycol is one or more of polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600, polyethylene glycol 800 and polyethylene glycol 1000. The present invention uses polyethylene glycol to achieve wet adhesion, and a supramolecular dynamic bond is formed between the phenylboronic acid group and the glycol of polyethylene glycol, and a sol-gel transition is achieved under alkaline conditions, thereby realizing the preparation of a bioadhesive that can be used for wet adhesion. During this process, the cross-linking effect between phenylboronic acid and the polyethylene glycol molecular chain is enhanced, so that the viscosity of the solution increases and a three-dimensional network structure is gradually formed, thereby achieving gelation. This sol-gel transition process is reversible and depends on changes in pH. In an alkaline environment, the gel can maintain stable adhesion, and when the pH returns to neutral or acidic, the borate bond dissociates, the gel network structure is destroyed, and the material returns to a sol state. The bioadhesive can provide a stable adhesion effect under wet conditions, and at the same time has dynamic responsiveness to adapt to changes in the pH environment during wound healing.
[0015] At the same time, as the molecular weight of polyethylene glycol increases, the cross-linking network strength of the material increases, and the bonding strength of the adhesive increases. For example, polyethylene glycol 200 and polyethylene glycol 400 have high fluidity and can be used in scenarios where wounds need to be covered quickly, while polyethylene glycol 800 and polyethylene glycol 1000 can increase the thickness and viscosity of the adhesive and are suitable for applications that require higher adhesion and support. Therefore, by increasing the polyethylene glycol segment to construct a multi-scale network structure, the cohesion and adhesion of the adhesive can be improved under wet conditions. The density of the network structure has an important influence on the degradation rate of the adhesive. Polyethylene glycol with a lower molecular weight (such as polyethylene glycol 200 and polyethylene glycol 400) has a poor density and can accelerate the degradation rate of the material, while polyethylene glycol with a higher molecular weight (such as polyethylene glycol 800 and polyethylene glycol 1000) helps to prolong the degradation time of the material in the body. By adjusting the type and proportion of polyethylene glycol, it can adapt to different wound healing stages or different treatment needs. On this basis, polyethylene glycol is sensitive to changes in the pH of the solution and can be used as a mild pH adjusting ingredient to help control the pH value of the adhesive in different environments and maintain its stability and functionality during the wound healing process.
[0016] Preferably, the pH regulator is a KOH aqueous solution, and the concentration of the KOH aqueous solution is 0.5-1.5 M. More preferably, it is 1 M. The alkaline environment provided by the pH range between 7.5 and 8 helps the cross-linking reaction between the cross-linking agent and chitosan to proceed more efficiently, forming a uniform network structure. This uniform cross-linked network helps to improve the mechanical strength and durability of the adhesive.
[0017] Preferably, the pH-responsive chitosan medical bioadhesive can respond to local pH changes at different wound healing stages and automatically adjust its degradation rate according to these pH changes to optimize the wound healing process, specifically including:
[0018] Early stage of wound healing (inflammatory stage):
[0019] Due to the metabolites (such as lactic acid) and cytokines (such as interleukins, tumor necrosis factor, etc.) produced during the inflammatory response, the wound area usually presents an acidic environment (pH value is about 5.5-6.5). In an acidic environment, the degradation rate of pH-responsive chitosan medical bioadhesive is slow. At this time, the adhesive can provide a long-lasting physical barrier to protect the wound, prevent bacterial invasion, and maintain a moist healing environment.
[0020] Mid-wound healing phase (proliferative phase):
[0021] As inflammation subsides and tissue repair proceeds, the local pH value begins to gradually recover toward neutrality. At this time, the wound begins to produce new tissues, such as granulation tissue, and angiogenesis and epithelial cell migration are accelerated. During the gradual recovery of pH, the degradation rate of the adhesive increases moderately. Appropriate degradation allows the adhesive to gradually release its components, which helps to provide continuous nutrition and growth factors, supporting cell migration and tissue reconstruction.
[0022] Late wound healing (remodeling phase):
[0023] In the later stage of wound healing, the pH value of the local environment returns to a value close to normal physiological pH (7.2-7.4). At this stage, tissue remodeling and complete wound closure are gradually completed. When the pH value is close to normal, the degradation rate of pH-responsive adhesives is further accelerated. This accelerated degradation process allows the adhesive to be quickly absorbed or excreted by the organism without interfering with the new tissue, which helps complete healing.
[0024] The present invention responds to local pH changes and regulates degradation time, and the pH-responsive chitosan medical bioadhesive provides personalized and dynamic support throughout the wound healing process. It can provide continuous barrier protection to prevent early infection; it degrades in time at the end of healing and is absorbed or metabolized by the organism, reducing the risk of long-term retention of foreign materials in the body and the probability of adverse reactions. This controllable degradation property ensures that the adhesive can exert its therapeutic effect while minimizing potential side effects on patients, thereby improving the safety and effectiveness of the overall treatment.
[0025] The second object of the present invention is to provide a one-pot preparation method of a pH-responsive chitosan medical bioadhesive, which avoids multi-step separation and purification operations by sequentially adding different components in the same reactor, simplifies the preparation process, reduces experimental steps and required equipment, and reduces operational complexity and production costs.
[0026] The above technical objectives of the present invention are achieved through the following technical solutions:
[0027] A method for preparing a pH-responsive chitosan medical bioadhesive comprises the following steps:
[0028] Add phenylboronic acid-modified chitosan to PBS buffer and stir evenly at room temperature; then add polyphenol compounds and stir evenly at 40°C; then add cross-linking agents with different functional groups and polyethylene glycols with different molecular weights in sequence and stir evenly; finally, add a pH regulator to adjust the pH of the system to 7.5-8, and leave it at room temperature for 1-3 hours to form a network structure, thereby obtaining the pH-responsive chitosan medical bioadhesive.
[0029] Preferably, the pH of the PBS buffer is 7-8, and the concentration is 0.01-0.03M.
[0030] Preferably, the pH adjuster is slowly added dropwise while keeping the solution evenly stirred at a rate of 1 drop / second until the pH reaches 7.5-8.
[0031] The third object of the present invention is to provide an application method of a pH-responsive chitosan medical bioadhesive, which has the same technical effect.
[0032] The above technical objectives of the present invention are achieved through the following technical solutions:
[0033] The pH-responsive chitosan medical bioadhesive is used to prepare a non-toxic and controllably degradable adhesive in vivo. In wound repair after surgery, the pH-responsive chitosan adhesive can be used as a biodegradable sealant to provide an immediate mechanical barrier, reduce the risk of postoperative infection, and gradually degrade during the healing process. Specifically, it can be applied to human organs, intestines, muscles, and oral cavity. The adhesive can adhere to damaged mucosa, provide a protective barrier to prevent further damage, and gradually degrade to avoid secondary intervention.
[0034] In the present invention, healing time refers to the time period from wound occurrence to complete healing. Adhesive degradation time refers to the time required for the adhesive to gradually decompose in the body and lose its adhesive effect. Ideally, the adhesive application area is slightly larger than the wound area to ensure complete coverage and an effective healing environment; the adhesive degradation time should match the wound healing time. Specifically, when applying, the adhesive can be selected according to the wound condition, including the following steps:
[0035] S1: creating a first data set containing wound information, the first data set including several groups of data, each group of data including wound type, initial pH value of wound, healing time, wound area, wound depth, wound location, patient's age, gender, health status and other characteristics;
[0036] S2: Create a second data set containing different adhesive properties. The second data set includes several groups of data, each of which includes adhesive type, use environment pH, use area, use amount, degradation time and other characteristics.
[0037] S3: Clean the first and second data sets to ensure that all features are normal, and then perform standardization;
[0038] S4: Extract all relevant features that affect the healing time from the first data set, take the healing time as the dependent variable, and the wound area, wound depth, wound location, patient's age, gender, health status and other factors as independent variables to establish a multiple regression model 1; extract all relevant features that affect the amount of adhesive used during treatment from the second data set, take the adhesive type, use environment pH, use area, degradation time and other factors as independent variables, and use amount as the dependent variable to establish a multiple regression model 2;
[0039] S5: In actual application, after inputting the patient's wound data information, the program uses a multivariate regression model to predict the healing time based on the data information;
[0040] S6: creating a number of input data sets equal to the number of adhesive types, wherein the input data sets include adhesive type, use environment pH, use area, and degradation time, wherein the use area is 1.2 times the wound area, the use environment pH is the initial pH value of the wound, and the degradation time is the predicted healing time;
[0041] S7: inputting each input data set into the multivariate regression model 2, and outputting the corresponding usage of equal quantities;
[0042] S8: Establish an optimization model that combines the usage and patient characteristics of multiple groups of adhesives output by multivariate regression model 2, calculates the total suitability score of each adhesive, selects the adhesive with the highest score and its dosage, and ensures that the recommended adhesive can maximize the efficacy and completely degrade after wound healing.
[0043] The total adaptability score is calculated based on the degree of match between the adhesive properties and the patient characteristics. The formula is as follows:
[0044] Total score = α × amount of adhesive used + β × patient age + γ × patient health status
[0045] Specifically, α, β, and γ are weight coefficients, and each weight coefficient can be obtained by expert experience method, regression analysis, etc. Each weight coefficient can also be tuned by cross validation, grid search, or Bayesian optimization to achieve the best prediction effect. The program outputs the adhesive type with the highest total adaptability score as a recommendation and provides relevant parameters. The output can be displayed in text form or in the form of detailed information cards or reports in a graphical interface.
[0046] In summary, the present invention has the following beneficial effects:
[0047] (1) The present invention innovatively introduces polyphenol compounds by modifying chitosan and combining it with the adhesion protein mechanism of marine organism mussels. The material behavior is given controllable properties under the action of pH-responsive sol-gel, providing dynamic needs for wound healing on the basis of wound closure. The pH-responsive bioadhesive meets high standards of environmental protection and biosafety, and can be applied to human organs, intestines, muscles, and oral cavity, etc. It also greatly broadens its potential application range in biomedical engineering and brings innovative solutions to the medical and health industry. Due to its controllable degradation characteristics, the adhesive does not need to be removed after use in the body, reducing the risk of secondary surgery and medical costs, and reducing the pain of patients. The antibacterial and anti-inflammatory properties of the adhesive also help reduce the risk of infection and provide a safer environment for wound healing.
[0048] (2) The pH-responsive chitosan medical bioadhesive of the present invention has good mechanical properties and material stability. Through the use of cross-linking agents and the formation of network structures, the adhesive can adapt to the dynamic changes of wounds or tissues while providing long-lasting adhesion, preventing failure in the biological environment. The adjustability of physical properties also makes it possible to optimize the properties of the adhesive by adjusting the molecular weight of polyethylene glycol and the type of cross-linking agent according to different application requirements. In terms of preparation process, the present invention adopts a one-pot preparation process, which is simple and efficient to operate, can be carried out under mild conditions, and maintains the active ingredients and functional properties of the material. This method not only saves time and cost, but is also suitable for industrial-scale production, ensuring the quality stability and consistency of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments described in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0050] Figure 1 This is a scanning electron microscope picture of the pH-responsive chitosan medical bioadhesive material after freeze-drying in Example 2 of the present invention. DETAILED DESCRIPTION
[0051] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, a pH-responsive chitosan medical bioadhesive and its preparation and application method proposed in the present invention, its specific implementation method, characteristics and effects are described in detail as follows.
[0052] Example 1
[0053] The present embodiment provides a pH-responsive chitosan medical bioadhesive and a one-pot preparation method thereof, comprising the following raw materials in parts by weight: adding 2% w / w phenylboronic acid-modified chitosan to PBS buffer (pH=7.4, concentration 0.01M), and stirring evenly at room temperature; then, adding 1% w / w dopamine and stirring evenly at 40°C; adding 0.3% w / w genipin and stirring evenly; adding 1.6% w / w polyethylene glycol 200 and stirring evenly; adding 1 M KOH aqueous solution to adjust the pH of the system to 7.6, and leaving it at room temperature for 2 hours to obtain the pH-responsive chitosan medical bioadhesive.
[0054] Example 2
[0055] This embodiment is basically the same as embodiment 1, except that the cross-linking agent used in this embodiment is replaced by glutaraldehyde.
[0056] Example 3
[0057] This embodiment is basically the same as Embodiment 1, except that the cross-linking agent used in this embodiment is replaced by ethylene glycol diglycidyl ether.
[0058] Example 4
[0059] This embodiment is substantially the same as Embodiment 1, except that the cross-linking agent used in this embodiment is replaced by isophorone diisocyanate.
[0060] Example 5
[0061] This embodiment is basically the same as embodiment 1, except that the polyethylene glycols of different molecular weights used in this embodiment are replaced with polyethylene glycol 400.
[0062] Example 6
[0063] This embodiment is basically the same as embodiment 1, except that the polyethylene glycols of different molecular weights used in this embodiment are replaced with polyethylene glycol 600.
[0064] Example 7
[0065] This embodiment is basically the same as embodiment 1, except that the polyethylene glycols of different molecular weights used in this embodiment are replaced with polyethylene glycol 800.
[0066] Example 8
[0067] This example is basically the same as Example 1, except that the polyethylene glycols of different molecular weights used in this example are replaced with polyethylene glycol 1000.
[0068] Comparative Example 1
[0069] The present embodiment provides a pH-responsive chitosan medical bioadhesive and a one-pot preparation method thereof, comprising the following raw materials in parts by weight: adding 2% w / w phenylboronic acid-modified chitosan to PBS buffer (pH=7.4, concentration 0.01M), and stirring evenly at room temperature; then, adding 1% w / w dopamine and stirring evenly at 40°C; adding 1.6% w / w polyethylene glycol 200 and stirring evenly; adding 1 M KOH aqueous solution to adjust the pH of the system to 7.6, and leaving it at room temperature for 2 hours to obtain the pH-responsive chitosan medical bioadhesive.
[0070] Comparative Example 2
[0071] The present embodiment provides a pH-responsive chitosan medical bioadhesive and a one-pot preparation method thereof, comprising the following raw materials in parts by weight: adding 2% w / w phenylboronic acid-modified chitosan to PBS buffer (pH=7.4, concentration 0.01M), and stirring evenly at room temperature; then, adding 1% w / w dopamine and stirring evenly at 40°C; adding 0.3% w / w genipin and stirring evenly; adding 1 M KOH aqueous solution to adjust the pH of the system to 7.6, and leaving it at room temperature for 2 hours to obtain the pH-responsive chitosan medical bioadhesive.
[0072] Performance evaluation method and implementation standards:
[0073] 1. Study on the adhesion properties of medical bioadhesives
[0074] The above examples and comparative examples were molded into test specimens and subjected to a 180-degree peel test according to ASTM F2256. All tests were performed at a speed of 50 mm min. -1 The peeling speed was constant; the standard shear adhesion test was carried out according to ASTM F2255, and all tests were carried out at a constant peeling speed of 50 mm / min. -1 The test was carried out at a constant peeling speed. All pigskins were soaked in phosphate buffer solution for 24 hours before testing. The internal environment of the human body is usually kept moist, which places special requirements on the adhesion and compatibility of the materials. When testing biomaterials, in order to ensure the accuracy of the test results and the relevance to clinical applications, the experimental conditions are simulated in a moist environment. Under such simulated conditions, the adhesion and stability of the materials can be evaluated more realistically, providing predictions for the performance of the materials in actual medical applications.
[0075] 2. Study on the in vitro degradation performance of medical bioadhesives
[0076] Accurately weigh the initial mass of the material to be tested and immerse it completely in the pre-prepared phosphate buffered saline (PBS) containing 0.2 mg / mL lipase. Place the sample in a constant temperature shaking water bath at 37°C, remove the sample and rinse it thoroughly with deionized water, and record the weight after vacuum drying.
[0077] 3. Detection of antibacterial rate against Escherichia coli
[0078] Table 1 Performance test results of Examples 1 to 8 and Comparative Examples 1 to 2
[0079]
[0080] As can be seen from Table 1, Examples 1 to 8 have excellent adhesion properties, because dopamine can give the material rich catechol groups. The reason why mussels can achieve super strong adhesion in different environments and interfaces is that the mussel foot protein contains a large amount of catechol, which forms a strong coordination effect with the surface of metals and their oxides, forms a hydrogen bond effect with the surface of inorganic non-metals, forms a π-π stacking effect with the surface of organic polymers, and forms Michael addition and Schiff base reactions with the surface of organisms after oxidation, and ion-π and spatial association effects mediated by acid / basic amino acids, thereby achieving strong adhesion. Tannic acid is introduced into the composite material to enhance the adhesion strength of the material by physical crosslinking. However, this physical crosslinking method is not stable and may lead to a decrease in adhesion performance under certain conditions. Therefore, although the introduction of tannic acid can improve the adhesion performance of the material to a certain extent, its stability problem still needs further research and improvement. At the same time, the phenylboronic acid group can form a supramolecular dynamic bond with the glycol of polyethylene glycol, and this supramolecular bond is pH-sensitive, breaking at acidic pH and regenerating at alkaline pH, giving the material pH-responsive and self-healing properties.
[0081] As shown in Table 1, from the performance test results of Examples 1 to 8 and Comparative Example 1, it can be seen that the composite material without the addition of a crosslinking agent is unable to be formed. This phenomenon can be attributed to the fact that Comparative Example 1 without the addition of a crosslinking agent cannot provide crosslinking sites for polymer crosslinking. At the same time, the material without the addition of a crosslinking agent cannot achieve a rapid chain growth process and cannot be formed due to the small initial molecular weight of the premixed solution.
[0082] As can be seen from Table 1, from the performance test results of Examples 1 to 4, it can be seen that different types of cross-linking agents have different effects on the shear viscosity of the adhesive. Genipin is one of the active ingredients of the traditional Chinese medicine Eucommia ulmoides, and is obtained by separation and purification of genipin glycoside. Genipin is a heterocyclic compound containing multiple active groups such as -OH, -COO-, which can form stable chemical bonds with a variety of biomacromolecules, has a good cross-linking effect and excellent biocompatibility, therefore, the introduction of genipin greatly improves the adhesion strength of the material. The introduction of traditional cross-linking agents such as dialdehyde cross-linking agents (glutaraldehyde and 2,5-furandicarboxaldehyde), epoxy cross-linking agents (ethylene glycol diglycidyl ether, polypropylene glycol glycidyl ether and triphenol methane triglycidyl ether) and isocyanate cross-linking agents (isophorone diisocyanate and toluene diisocyanate) can make the material molded, but the adhesion strength is reduced compared with the adhesion strength of the adhesive using genipin. At the same time, compared with traditional permanent cross-linkers, genipin-cross-linked materials can gradually degrade in the body, reducing potential side effects after long-term implantation.
[0083] As shown in Table 1, from the performance test results of Examples 5 to 9 and Comparative Example 2, it can be seen that the material of Comparative Example 2 without adding polyethylene glycol cannot be formed. This is because the phenylboronic acid group forms a supramolecular dynamic bond with the glycol of polyethylene glycol, and the sol-gel transition is realized under alkaline conditions and then formed. At the same time, as the molecular weight of polyethylene glycol increases, the cross-linked network strength of the material increases, and the bonding strength of the adhesive increases. Therefore, by improving the polyethylene glycol segment to construct a multi-scale network structure, the cohesion and adhesion of the adhesive can be improved. The introduction of polyethylene glycol has an important influence on the wet adhesion performance of pH-responsive chitosan medical bioadhesive. Polyethylene glycol is a hydrophilic polymer, and its introduction can maintain adhesion in a humid or liquid environment. The hydrophilic functional groups of the polyethylene glycol molecular chain can form hydrogen bonds with water molecules, reduce the water molecule layer at the interface, and thus reduce the negative impact of the hydration layer on the adhesion between the adhesive and the tissue. The introduction of polyethylene glycol can also improve the flexibility and ductility of the adhesive, which helps the adhesive to better adapt to the irregular surface of the tissue and improve the adhesion area and adhesion. Polyethylene glycol with a lower molecular weight has a shorter molecular chain, so it has a higher fluidity in the adhesive network, can more effectively form hydrogen bonds with water molecules, and improve wettability. But at the same time, polyethylene glycol with a lower molecular weight may cause the adhesive network structure to be less dense and have poor adhesion strength; polyethylene glycol with a higher molecular weight has a longer molecular chain, which can form a denser three-dimensional network structure and increase the cohesion and adhesion strength of the adhesive. The entanglement of long-chain polyethylene glycol in the network can improve the mechanical strength and tensile resistance of the adhesive, thereby providing stronger adhesion under wet conditions. In addition, the chain segments formed by high molecular weight polyethylene glycol in the adhesive network can serve as physical cross-linking points to enhance the stability of the network, thereby maintaining a higher adhesion strength under wet conditions.
[0084] As can be seen from Table 1, from the performance test results of Examples 1 to 8, it can be seen that the pH-responsive chitosan medical bioadhesives of Examples 1 to 8 show excellent biodegradability, and their degradation period is 5 to 22 days. As a component of synthetic bioadhesives, the molecular weight of polyethylene glycol directly affects the physicochemical properties of the material. Polyethylene glycol with a lower molecular weight (such as polyethylene glycol 200) may have a faster degradation rate, and the degradation period of Example 1 is 14 days, because smaller molecules are more easily decomposed by enzymes in the body, thereby accelerating the overall degradation process of the adhesive. Polyethylene glycol with a higher molecular weight (such as polyethylene glycol 1000) forms a denser network structure and a relatively slow degradation rate. The degradation period of Example 8 is 21 days, because the interaction between the macromolecular chains is enhanced, making it difficult for the enzyme to approach and decompose the material. At the same time, the choice of cross-linking agent plays a decisive role in the stability and degradability of the adhesive. The cross-linking agent connects polyethylene glycol and modified chitosan into a three-dimensional network structure by forming chemical bonds. As a natural cross-linking agent, genipin contains multiple active groups, which can form stable chemical bonds and improve the adhesion strength of the adhesive. Genipin has good biocompatibility and can be gradually degraded in the body, reducing the side effects of long-term implantation. Traditional cross-linking agents such as glutaraldehyde, 2,5-furandicarboxaldehyde, etc., also help to reduce the degradation time. The degradation cycle of Example 2 is 12 days. Epoxy cross-linking agents and isocyanate cross-linking agents have relatively low cross-linking activity, so the degradation cycle of the adhesive is reduced. The degradation cycle of Examples 3 and 4 is reduced to 5 and 7 days. Therefore, precise control of the degradation cycle is crucial for medical adhesives. It ensures that the adhesive can be cleared by the organism in time after completing its function, reducing the long-term impact on surrounding tissues. Through our screening of polyethylene glycol molecular weight and cross-linking agent types, precise control of the material degradation cycle is achieved. At the same time, precise control of the degradation cycle not only meets clinical needs, but also meets the safety and effectiveness standards of biomaterials. The cross-linking agent and polyphenol compound selected in the present invention not only provide the necessary mechanical strength and adhesion performance, but also ensure that the material can be safely degraded within a specific time in the body, thereby avoiding the potential risk of long-term existence in the body.
[0085] Antibacterial property is one of the key indicators for evaluating the safety of medical adhesives. A high antibacterial rate not only helps prevent surgical site infections, but also promotes wound healing and reduces the risk of postoperative complications in patients. As can be seen from Table 1, from the performance test results of Examples 1 to 8, it can be seen that the pH-responsive chitosan medical bioadhesives of Examples 1 to 8 also have significant antibacterial properties. In the antibacterial test on Escherichia coli, the adhesive showed an antibacterial rate of up to 99%. This efficient antibacterial effect is mainly attributed to the antibacterial properties of chitosan itself and the synergistic effect of polyphenolic compounds. The hydroxyl groups contained in polyphenolic compounds can form hydrogen bonds with proteins on the bacterial cell wall, interfering with the normal metabolism and reproduction of bacteria, thereby achieving an antibacterial effect.
[0086] The pH-responsive chitosan medical bioadhesive provided by the present invention has excellent adhesion in vivo and can achieve instant adhesion to organs, intestines and muscles of living rabbits during animal experiments.
[0087] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A pH-responsive chitosan medical bioadhesive, characterized in that: The invention comprises phenylboronic acid modified chitosan, polyphenolic compounds, a pH regulator, a crosslinking agent and polyethylene glycol; the mass concentration of the phenylboronic acid modified chitosan is 1.3-13% w / w; the mass concentration of the polyphenolic compounds is 0.1-2% w / w; the mass concentration of the crosslinking agent is 0.2-2% w / w; the mass concentration of the polyethylene glycol is 1.0-10.4% w / w; and the pH regulator is used to adjust the pH value in the system to 7.5-8.
2. The pH-responsive chitosan medical bioadhesive according to claim 1, characterized in that: The polyphenolic compounds include one or more of tea phenol, gallic acid, tannic acid, tannic acid, catechin, 3,4-dihydroxyphenylacetic acid, 2,3-dihydroxybenzoic acid and dopamine.
3. The pH-responsive chitosan medical bioadhesive according to claim 1, characterized in that: The cross-linking agent is one or more of genipin, glutaraldehyde, 2,5-furandicarboxaldehyde, ethylene glycol diglycidyl ether, polypropylene glycol glycidyl ether, triphenol methane triglycidyl ether, isophorone diisocyanate, and toluene diisocyanate.
4. The pH-responsive chitosan medical bioadhesive according to claim 1, characterized in that: The polyethylene glycol is one or more of polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 600, polyethylene glycol 800 and polyethylene glycol 1000.
5. The pH-responsive chitosan medical bioadhesive according to claim 1, characterized in that: The pH regulator is a KOH aqueous solution, and the concentration of the KOH aqueous solution is 0.5-1.5 M.
6. A pH-responsive chitosan medical bioadhesive according to any one of claims 1 to 5, characterized in that: The pH-responsive chitosan medical bioadhesive can respond to local pH changes at different wound healing stages and regulate degradation time.
7. The method for preparing a pH-responsive chitosan medical bioadhesive according to claim 1, characterized in that: The steps are as follows: Add phenylboronic acid-modified chitosan to PBS buffer and stir evenly at room temperature; then add polyphenol compounds and stir evenly at 40°C; then add cross-linking agent and polyethylene glycol in sequence and stir evenly; finally add pH regulator to adjust the pH of the system to 7.5-8, and leave at room temperature to form a network structure to obtain the pH-responsive chitosan medical bioadhesive.
8. The method for preparing a pH-responsive chitosan medical bioadhesive according to claim 7, characterized in that: The pH of the PBS buffer is 7-8, and the concentration is 0.01-0.03M.
9. The method for preparing a pH-responsive chitosan medical bioadhesive according to claim 8, characterized in that: The pH adjuster was slowly added dropwise, and the solution was stirred evenly at a rate of 1 drop / second until the pH reached 7.5-8.
10. Using the pH-responsive chitosan medical bioadhesive as claimed in claim 1 to prepare a non-toxic and controllably degradable adhesive in vivo.
Citation Information
Patent Citations
Novel polysaccharide cellulose medical gum with high mechanical strength and capability of promoting wound healing and preparation method of novel polysaccharide cellulose medical gum
CN106110376A
Preparation method of medical adhesive
CN106512078A
Biomedical adhesive and preparation method thereof
CN106075553A
pH sensitive hydrogel as well as preparation method and application thereof
CN107325300A